Assembly In Vitro of Tau Protein and its Implications in Alzheimer's Disease - Avila, Jesus; Perez, Mar; Lucas, Jose J.; Gomez-Ramos, Alberto; Maria, Ismael S.; Moreno, Francisco; Smith, Mark; Perry, George; Hernandez, Felix (Current Alzheimer Research, 2004)
Tau is a microtubule associated protein that is also the main component of the aberrant filaments that form aberrant structures like the neuropil threads or the neurofibrillary tangles, found in the brain of Alzheimer's disease patients. The assembly of tau aberrant filaments could be reproduced in vitro by using a high concentration of tau protein or, at lower protein concentrations, by adding some compounds like polyanions, fatty acids (and derivates), and others. In this mini-review a descriptive analysis of the different conditions needed for in vitro tau polymerization are summarized.
Keywords: assembly